Q. 7 B3.5( 35 Votes )

For some constant

Answer :

Let f(x) =


f(x) = a2x4 + 2abx2 + b2


So,



Since,


f’(x) = a2 × 4x3 + 2ab × 2x + 0


= 4a2x3 + 4abx


f’(x) = 4ax (ax2 + b)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar